Denmark’s Little Brother: The Image of Iceland in Adam Oehlenschläger’s Drama Palnatoke - Anežka Matěnová (Acta Universitatis Carolinae: Philologica)
The drama Palnatoke by Adam Oehlenschläger (1779–1850) tells the story of an alliance of Vikings who lay the foundation stones of the Danish state. The author of the article analyses the image of Iceland and Icelanders in the drama. The article argues that the friendly, peace-loving Icelandic protagonist who travels around the world stands for Scandinavianism, a movement promoting political and cultural cooperation of the Nordic countries. In addition, the character shows some features of the Beautiful as opposed to the Danish Sublime – he is partly feminised. As a result, he looks up to the Danes. Iceland and Denmark are not on an equal footing; Denmark’s attitude to Iceland is colonial and paternalistic. On the one hand, Iceland is praised for its literature and knowledge and Icelanders for their pure hearts. On the other hand, the Icelander is depicted as inferior and in a primitivistic way.